Pengaruh Kepuasan Kerja, Komitmen Organisasi dan Work Family Conflict terhadap Turnover Intention - Fida Larasati Gatiningtyas; Rasistia Wisandianing Primadineska (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the effect of job satisfaction, organizational commitment and work family conflict on turnover intention in the quality control department at PT Mataram Tunggal Garment. The data collection method used a questionnaire distributed via google form. The population of this research are production employees in the quality control department at PT Mataram Tunggal Garment. Sampling was done using Non-Probability Sampling with purposive sampling technique. The number of samples is 105 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the effect of job satisfaction, organizational commitment and work family conflict has a positive and significant effect on turnover intention in the quality control section at PT Mataram Tunggal Garment.